Double-Crop Sunflower Cost-Return Budget in Central and Kansas - O'Brien, Daniel M.; Duncan, Stewart R. (My University, 2009)
This publication provides estimated cost and returns for forward farm planning for a double-crop sunflower production system in central and eastern Kansas.
MF2145_2009_12
Keywords: MF2145; Crops; Economics; MF